Los indios de pueblos y misiones y el abasto de centros mineros del Septentrión novohispano. San Felipe el Real de Chihuahua a fines del siglo XVIII - Sara Ortelli (Centre de Recherches sur les Mondes Américains, 2011)
This article analyzes the participation of Indians of towns and missions in the supply of the mining center of San Felipe the Real Chihuahua in second half of 18th century. Take into account legal aspects of such participation (represented in the entrances of grains and flours to alhóndiga and the provision of manpower through repartimientos) and illegal circuits related to the provision of cattle and derived products. The main sources used for the reconstruction of these processes are the books that register the entrances to alhóndiga of Chihuahua, diverse information and opinions of civil servants about the repartimiento of indigenous manpower and files of criminal lawsuits by cattle robbery.